Illicit substance use among university students from seven European countries: A comparison of personal and perceived peer use and attitudes towards illicit substance use - AKVARDAR, YILDIZ (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2014)
Objective: To compare European students' personal use and approval of illicit substance use with their perceptions of peer behaviours and attitudes, and investigate whether perceptions of peer norms are associated with personal use of illicit substances and attitudes. Method: This study used baseline data from the Social Norms Intervention for the prevention of Polydrug usE (SNIPE) project involving 4482 students from seven European countries in 2012. Students completed an online survey which included questions on personal and perceived peer illicit substance use and personal and perceived peer attitude towards illicit substances. Results: 8.3% of students reported having used illicit substances at least once in their life. 49.7% of students perceived that the majority of their peers have used illicit substances more frequently than themselves. The perception was significantly associated with higher odds for personal illicit substance use (OR: 1.97, 95% Cl: 1.53-2.54). The perception that the majority of peers approve illicit substance use was significantly associated with higher odds for personal approval of illicit substance use (OR: 3.47,95% CI: 2.73-4.41). Conclusion: Students commonly perceived that their peers used illicit subtances more often than themselves. We found an association between the perceived peer norms/attitudes and reported individual behaviour/ attitudes. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Illicit drugs; Students; Europe; Health behaviour; COLLEGE DRINKING; INJUNCTIVE NORMS; DRUG-USE; SOCIAL NORMS; ALCOHOL-USE; MISPERCEPTIONS; PREVENTION; EXPECTANCIES; ADOLESCENTS; NATIONWIDE